After Marikana: Rethinking Conflict Resolution in Africa: The South African Case. Issue 1 (10th February 2015) - Bradshaw, Gavin; Haines, Richard
This paper applies the Analytical Conflict Resolution School approach to achieve a deeper understanding of South Africa's post-apartheid era. It argues that South Africa is an example of 'protracted social conflict, ' because it displays a fundamental communal aspect, evinces a strong 'human needs' element, its pre-settlement condition had resulted in strongly authoritarian government, and it displayed a dependency in its foreign relations. While South Africa transcended traditional conflict resolution methodology with its National Peace Accord and Truth and Reconciliation Commission, neither of these processes was seen through to its end and, as a result, the South African conflict resolution process remains in limbo. This is coupled with a rising internal level of strain expressed in racial tension, violence, migration and economic frustration. A way out of this current malaise is the institutionalization of conflict management through its inclusion in the school curricula, the establishment of conflict management systems to deal with lower-level conflicts, and the building of needs-satisfying institutional arrangements throughout the society, enabling government to be more sensitive to the needs of the people.